CLINICAL CHARACTERISTICS OF INTRAMEDULLARY SPINAL CORD TUMORS OF VARIOUS HISTOLOGICAL STRUCTURES : Literature review - Alikhodjayeva, G.A.; Akhmediev , T.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Intramedullary spinal cord tumors (IMSCT) make up from 2 to 4% of all tumors of the central nervous system. These neoplasms "traditionally" have a worse prognosis than extramedullary neoplasms. It is known that 90% of IMSCT are represented by low grade gliomas, which can be successfully removed. Ependymomas (63-65%) and astrocytomas (24.5–30%) constitute the main group of intramedullary spinal cord tumors, glioblastomas (7.5%), oligodendrogliomas (3%) and other tumors (2%) are much less common. The problem of timely detection of IMSCT remains relevant. Unlike brain tumors, these tumors are mostly benign. The clinical course of these tumors is most often acute. By the time obvious neurological signs appear, neurological disorders are already irreversible.